1993
DOI: 10.1111/j.1440-1746.1993.tb01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Small angiomyolipoma of the liver diagnosed by fine‐needle aspiration biopsy under ultrasound guidance

Abstract: The first reported case of small hepatic angiomyolipoma to be diagnosed by fine-needle aspiration biopsy (FNAB) is described. A 53 year old man presented with a tumour in segment VI of the liver measuring 0.9 x 0.8 cm. The tumour was hyperechoic on ultrasound examination, showed relatively low density (+ 33 Hounsfield units) on computed tomography (CT), and was hypervascular on angiography. Computed tomography during arterial portography demonstrated a perfusion defect. Magnetic resonance imaging (MRI) reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Seven AML tumors were detected incidentally at autopsy,3,5,8 and one at abdominal surgery;38 the remaining tumors in asymptomatic patients were incidentally detected during health examination or abdominal examination for other disease unrelated to the hepatic tumor. Of the symptomatic patients, 31 showed abdominal pain or distress ,11,13,14,16,17,19,22,23,,31,32,34,35,37,42,44,48,,54,56. 6 upper abdominal mass or hepatomegaly,11,25,27,34,35 7 malaise,8,15,18,28,46,47,51 2 night sweating,18,28 2 fever,8,40 1 tenderness8, 1 jaundice,10 1 anemia,8 1 palmar erythema,20 1 diarrhea,42 and 1 vomiting 45.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven AML tumors were detected incidentally at autopsy,3,5,8 and one at abdominal surgery;38 the remaining tumors in asymptomatic patients were incidentally detected during health examination or abdominal examination for other disease unrelated to the hepatic tumor. Of the symptomatic patients, 31 showed abdominal pain or distress ,11,13,14,16,17,19,22,23,,31,32,34,35,37,42,44,48,,54,56. 6 upper abdominal mass or hepatomegaly,11,25,27,34,35 7 malaise,8,15,18,28,46,47,51 2 night sweating,18,28 2 fever,8,40 1 tenderness8, 1 jaundice,10 1 anemia,8 1 palmar erythema,20 1 diarrhea,42 and 1 vomiting 45.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…We1 previously compiled a report of 52 cases of hepatic AML presented in the world literature and reviewed their clinical and pathologic features. Since that report was published, an additional 25 cases of hepatic AML have been reported 37,. We have also experienced 3 additional cases ourselves, resulting in a total of 9 AML tumors in 8 patients 57.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, several authors have suggested that this disease can be managed with conservative treatment 4–7. However, since 2000, several reports have revealed that this kind of tumor can be malignant with evidence of recurrence 810.…”
Section: Introductionmentioning
confidence: 99%
“…19 The first case diagnosed by FNA was in 1993, 20 followed by a few more papers describing the cytologic features of AML. [4][5][6][7][8] Unawareness of the existence of angiomyolipoma in the liver, and lack of experience may lead to misdiagnosis, especially on fine-needle aspirates. To complicate matters, hepatic angiomyolipoma has a resemblance to hepatocellular carcinoma in clinical presentation.…”
Section: Discussionmentioning
confidence: 99%